A Causal Role for the Right Dorsolateral Prefrontal Cortex in Avoidance of Risky Choices and Making Advantageous Selections. (15th March 2021) - Obeso, Ignacio; Herrero, Maria-Trinidad; Ligneul, Romain; Rothwell, John C.; Jahanshahi, Marjan
Graphical abstract: Highlights: Using theta burst stimulation we show the DLPFC as causally involved in risky decision-making. Inhibitory theta burst protocols over the right and left DLPFC decreased explorative behaviour. Inhibitory theta burst protocols over the right DLPFC enhanced sensitivity to reward value, resulting in risk avoidance. The right DLPFC directs behaviour to avoid risky choices and adopt more cautious but beneficial choices. Abstract: In everyday life, risky decision-making relies on multiple cognitive processes including sensitivity to reinforcers, exploration, learning, and forgetting. Neuroimaging evidence suggests that the dorsolateral prefrontal cortex (DLPFC) is involved in exploration and risky decision-making, but the nature of its computations and its causal role remain uncertain. We provide evidence for the role of the DLPFC in value-independent, directed exploration on the Iowa Gambling Task (IGT) and we describe a new computational model to account for the competition of directed exploration and exploitation in guiding decisions. Forty-two healthy human participants were included in a right DLPFC, left DLPFC or sham stimulation groups using continuous theta -burst stimulation (cTBS). Immediately after cTBS, the IGT was completed. Computational modelling was used to account for exploration and exploitation with different combinations with value-based and sensitivity to reinforcers for each group. Applying cTBS to the left and right DLPFC selectively decreased directed exploration on the IGT compared to sham stimulation. Model-based analyses further indicated that the right (but not the left) DLPFC stimulation increased sensitivity to reinforcers, leading to avoidance of risky choices and promoting advantageous choices during the task. Although these findings are based on small sample sizes per group, they nevertheless elucidate the causal role of the right DLPFC in governing the exploration–exploitation tradeoff during decision-making in uncertain and ambiguous contexts.